Land Elevation and Cancer Mortality in U.S. Cities and Counties using Median Elevations Derived from Geographic Information Systems - John Hart (SAGE Publishing, 2013)
There are a number of variables that are correlated with land elevation. Land elevation, and in particular, its surrogate variables such as natural background radiation, can be studied in relation to cancer rates. The present ecological study focuses on three such variables correlated with land elevation: natural background radiation (NBR), oxygen concentration (OC), and barometric pressure (BP). In addition, the study uses a novel approach for determining median land elevation values from which the surrogated variables are estimated. Inverse correlations were observed for NBR while direct correlations were found for OC and BP suggesting the presence of a protective effect with all three variables. Further study is indicated to either verify or refute these findings.